Breastfeeding practices among institutionally delivered newborns: a single centre experience - Bhatnagar, Ruchika; Gupta, Priyanshu; Bharti, Abhishek; Gupta, Brig Rakesh (Brazilian Journal of Biometrics, 2025)
With the rise in institutional deliveries, the responsibility of timely initiation and maintaining optimum breastfeeding practices has shifted from families and community health workers to doctors and nursing personnel. According to the National Family Health Survey - 5, there is significant rise in institutional births from 78.9 % to 88.6 % while early initiation of breastfeeding (EIBF) still ranges from 41.6% to 41.8%. The present study aimed to gain insights into the breastfeeding practices among institutionally delivered newborns, and determine the factors affecting it. This was a hospital based analytical cross-sectional study. After obtaining Institutional Ethics Committee approval and written informed consent, 375 postnatal mothers were interviewed within 24 hours of delivery. Breastfeeding practices were recorded and logistic regression analysis was performed to identify the determinants of EIBF and exclusive breastfeeding (EBF). Out of 375 respondents, only 143 mothers (39.2%) followed EIBF. Pre-lacteal feed was given by 112 mothers (30.7%), while EBF was practiced by 197 mothers (54%). On logistic regression analysis, mothers belonging to upper socio-economic status (p=0.001; AOR, 13.31; 95% CI, 2.8-62.5), normal vaginal delivery (p<0.001; AOR, 0.089; 95%CI,0.1-0.2) and multiparous mothers (p=0.006; AOR,2.494; 95% CI 1.3-4.7) were more likely to follow EIBF. Determinants of exclusive breastfeeding observed in this study was health seeking behavior of mothers as reflected through number of antenatal clinics attended (p=0.001; AOR, 5.298; 95%CI 0.3-0.7) and Caesarean delivery (p<0.001; AOR, 0.410; 95% CI, 0.3-0.7). Breastfeeding practices like timely initiation of breastfeeding and exclusive breastfeeding among the institutionally delivered newborns are comparatively low as opposed to the nation’s average value. Socio-economic profile, mode of delivery, parity, and health seeking behaviour of mothers proved to be the significant factors determining the breastfeeding practices. Antenatal counselling needs to be strengthened with identified bottlenecks like primiparous women, economically underprivileged mothers and mothers with caesarean delivery.